2019
DOI: 10.1111/mpp.12822
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dynamics and mitophagy are necessary for proper invasive growth in rice blast

Abstract: Summary Magnaporthe oryzae causes blast disease, which is one of the most devastating infections in rice and several important cereal crops. Magnaporthe oryzae needs to coordinate gene regulation, morphological changes, nutrient acquisition and host evasion in order to invade and proliferate within the plant tissues. Thus far, the molecular mechanisms underlying the regulation of invasive growth in planta have remained largely unknown. We id… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 39 publications
(69 reference statements)
2
33
0
Order By: Relevance
“…Mitochondria undergo dynamic morphological changes in response to environmental stress and nutrient availability has been shown to dictate mitochondrial morphology 7 , 21 , 43 . Our findings are consistent with previous studies demonstrating that nutrient starvation induces mitochondrial fission 44 46 and suggest that metabolic regulation of mitochondrial dynamics may be determined by NIK activity to promote metabolic reprogramming to OXPHOS and drive invasive growth. Indeed, analysis of RNA-seq data from the IVY Glioblastoma Atlas 47 revealed that genes regulating mitochondrial dynamics, including DRP1, as well as mitochondrial respiratory complexes are more highly expressed at the tumor leading edge compared to the tumor core (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Mitochondria undergo dynamic morphological changes in response to environmental stress and nutrient availability has been shown to dictate mitochondrial morphology 7 , 21 , 43 . Our findings are consistent with previous studies demonstrating that nutrient starvation induces mitochondrial fission 44 46 and suggest that metabolic regulation of mitochondrial dynamics may be determined by NIK activity to promote metabolic reprogramming to OXPHOS and drive invasive growth. Indeed, analysis of RNA-seq data from the IVY Glioblastoma Atlas 47 revealed that genes regulating mitochondrial dynamics, including DRP1, as well as mitochondrial respiratory complexes are more highly expressed at the tumor leading edge compared to the tumor core (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, further examination of mitophagy in M. oryzae revealed that the loss of Atg24 results in delayed appressorium infectivity and reduced growth of the invasive hyphae. In line with these findings, Atg24-dependent vacuolar degradation of mitochondria was observed during the initial stages of the plant infection [122]. These observations disclosed that Atg24-driven mitophagy is required for the establishment of the blast disease.…”
Section: Mitophagy and Pexophagy Are Required For Pathogenic Developmsupporting
confidence: 79%
“…As for M. oryzae , Dnm1 is required for full virulence in the corn smut fungus Ustilago maydis [ 121 ]. Additionally, the deletion of the fusion machinery gene FZO1 also results in decreased infective growth and reduced appressoria penetration capability in M. oryzae [ 122 ].…”
Section: Peroxisome and Mitochondrial Dynamics Are Required For Pamentioning
confidence: 99%
“…The fact that during infection this fungus is exposed to high ROS levels, suggests that H 2 O 2 produced by the plant could induce mitochondrial fission. Carbon starvation has been proposed as the trigger of mitochondrial fragmentation under these conditions (Kou et al, 2019). However, both factors might contribute to this process.…”
Section: Mitochondrial Fission Is Connected To Development and Inducementioning
confidence: 99%